Review: Mechanisms and perspective treatment of radioresistance in non-small cell lung cancer - Zhou, Ting; Zhang, Li-Ying; He, Jian-Zheng; Miao, Zhi-Ming; Li, Yang-Yang; Zhang, Yi-Ming; Liu, Zhi-Wei; Zhang, Shang-Zu; Chen, Yan; Zhou, Gu-Cheng; Liu, Yong-Qi (Frontiers in Immunology, 2023)
Radiotherapy is the major treatment of non-small cell lung cancer (NSCLC). The radioresistance and toxicity are the main obstacles that leading to therapeutic failure and poor prognosis. Oncogenic mutation, cancer stem cells (CSCs), tumor hypoxia, DNA damage repair, epithelial-mesenchymal transition (EMT), and tumor microenvironment (TME) may dominate the occurrence of radioresistance at different stages of radiotherapy. Chemotherapy drugs, targeted drugs, and immune checkpoint inhibitors are combined with radiotherapy to treat NSCLC to improve the efficacy. This article reviews the potential mechanism of radioresistance in NSCLC, and discusses the current drug research to overcome radioresistance and the advantages of Traditional Chinese medicine (TCM) in enhancing the efficacy and reducing the toxicity of radiotherapy.